Antibody phage-displayed libraries derived from chicken immunoglobulin genes : a source of highly specific diagnostic antibodies - Du Plessis, Dion H. (University of Pretoria, 2013)
Dissertation (MSc (Veterinary Science))--University of Pretoria, 2007.